2011
DOI: 10.1103/physrevb.84.104203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of medium-range order on the glass transition in liquid Ni-Si alloys

Abstract: We study the thermophysical properties and structure of liquid Ni-Si alloys using molecular dynamics simulations. The liquid Ni-5% and 10%Si alloys crystallize to form face-centered cubic (Ni) at 900 and 850 K respectively, and the glass transitions take place in Ni-20% and 25%Si alloys at about 700 K. The temperature dependent self-diffusion coefficients and viscosities exhibit more pronounced non-Arrhenius behavior with the increase of Si content before phase transitions, indicating the enhanced glass-formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The similar conclusion was drawn by Wu et al [452]. Lü and Entel also found by numerical simulations that a Ni-Si system has fcc-like MRCO, which is perturbed by the addition of Si atoms [453]. Liu et al found that glass transition can be seen as a process of increasing MRCO [454].…”
Section: A Case Of Metallic Glass-forming Systemssupporting
confidence: 72%
“…The similar conclusion was drawn by Wu et al [452]. Lü and Entel also found by numerical simulations that a Ni-Si system has fcc-like MRCO, which is perturbed by the addition of Si atoms [453]. Liu et al found that glass transition can be seen as a process of increasing MRCO [454].…”
Section: A Case Of Metallic Glass-forming Systemssupporting
confidence: 72%
“…9. [36] Table 5. Ratios of the second, third, and fourth peak positions in RDF to the nearest neighboring distance for Cu-H and Zr-H pairs.…”
Section: Resultsmentioning
confidence: 99%
“…influenced by the composition and by process parameters like cooling rate and melt undercooling [5,6]. MD-simulations showed that the molar volume of a NiSi melt decreases at first with rising Si concentration hinting to strong interactions between the particles [7]. A consequence of this mixing effect might be the tendency for an increased glass forming ability with increasing Si content [7].…”
Section: Introductionmentioning
confidence: 99%
“…MD-simulations showed that the molar volume of a NiSi melt decreases at first with rising Si concentration hinting to strong interactions between the particles [7]. A consequence of this mixing effect might be the tendency for an increased glass forming ability with increasing Si content [7]. For example, the eutectic composition Ni 78.6 Si 21.4 can be undercooled several hundreds K [8].…”
Section: Introductionmentioning
confidence: 99%